Penerapan H5P Guna Pengembangan Media Edukasi Keamanan Siber di SMPN 14 Kota Madiun - Andria, Andria; Ridam Dwi Laksono; Kelik Sussolaikah; Hani Atun Mumtahana (Infotek: Jurnal Informatika dan Teknologi, 2024)
In the learning process innovation is needed, including educational media that can be used to support learning activities, including cyber security material that needs to be conveyed to students in order to grow and improve digital literacy skills. Monotonous learning can have an impact on students, including making students feel bored and lazy. This research aims to implement H5P as a web-based framework that provides access to various interactive content for the development of educational media regarding cyber security at SMPN 14 Madiun so that the learning process can be presented in the form of interesting and interactive content. The method used in this research is Research and Development (RnD), utilizing LMS Moodle as a learning media platform that is free and can be developed according to needs. The results of this research show that the application of H5P can help teachers create various types of interactive content such as presentations, videos, quizzes, and so on. Students can play and learn at the same time through LMS Moodle, which has implemented the H5P plugin for interactive content so that they can improve their digital literacy skills, especially understanding cyber security in the era of digitalization